Reflections on the Decision-Making Process based on Institutional Logics - Teixeira, Maisa Gomide; Roglio, Karina De Déa; Ferreira, Jane Mendes (Revista de Administração da UFSM, 2017)
Studies on organizational decision-making process indicate the importance of adopting new theoretical perspectives that enable advances in understanding this process. Thus, in this essay we analyze the decision-making process from the perspective of institutional logics, considering the influences of multiple rationalities in this process. As references for this analysis, we present the development of knowledge on decision making process, institutional logics as a recent approach of sociological institutionalism; hybridity of institutional logics, relations between fields of institutionalism and decision making. The paper’s contribution is anchored in three points. First, there is a relationship between institutional logics and the decisions taken in organizations. Second, using this conception allows a broader understanding about conflicts and inconsistencies that promote opportunities for agency and variability on practices, considering action as socially embedded. Finally, by integrating hybridism in studies of decision making process broadens knowledge about organizational change as it depends on decisions about which elements of organizational forms should be retained or replaced.